Deregulation of a Cis-Acting lncRNA in Non-small Cell Lung Cancer May Control HMGA1 Expression - Stewart, Greg L.; Sage, Adam P.; Enfield, Katey S. S.; Marshall, Erin A.; Cohn, David E.; Lam, Wan L. (Frontiers in Genetics, 2021)
Background: Long non-coding RNAs (lncRNAs) have long been implicated in cancer-associated phenotypes. Recently, a class of lncRNAs, known as cis-acting, have been shown to regulate the expression of neighbouring protein-coding genes and may represent undiscovered therapeutic action points. The chromatin modifying HMGA1 has recently been described to be aberrantly expressed in lung adenocarcinoma (LUAD). However, the mechanisms mediating HMGA1 in LUAD remain unknown. Here we investigate the deregulation of a putative cis-acting lncRNA in LUAD, and its effect on the oncogene HMGA1. Methods: LncRNA expression was determined from RNA-sequencing data of tumour and matched non-malignant tissues from 36 LUAD patients. Transcripts with significantly deregulated expression were identified and validated in a secondary LUAD RNA-seq dataset (TCGA). SiRNA-mediated knockdown of a candidate cis-acting lncRNA was performed in BEAS-2B cells. Quantitative real-time PCR was used to observe the effects of lncRNA knockdown on the expression of HMGA1. Results: We identified the lncRNA RP11.513I15.6, which we refer to as HMGA1-lnc, neighbouring HMGA1 to be significantly downregulated in both LUAD cohorts. Conversely, we found HMGA1 significantly overexpressed in LUAD and anticorrelated with HMGA1-lnc. In vitro experiments demonstrated siRNA-mediated inhibition of HMGA1-lnc in immortalized non-malignant lung epithelial cells resulted in a significant increase in HMGA1 gene expression. Conclusion: Our results suggest that HMGA1-lnc is a cis-acting lncRNA that negatively regulates HMGA1 gene expression in lung cells. Further characterization of this regulatory mechanism may advance our understanding of the maintenance of lung cancer phenotypes and uncover a novel therapeutic intervention point for tumours driven by HMGA1.